Analysis of scientific production through the interdisciplinarity between the Information Science and the Administration in the organizational environments - Pinheiro dos Santos, Beatriz Rosa [UNESP]; Biaggi, Camila de [UNESP]; Martins Damian, Ieda Pelogia; Bassan de Moraes, Cassia Regina (Univ Brasilia, Dept Ciencia Informacao, 2019)
The text is a literature review based on a scientometric analysis on the interdisciplinarity between the scientific fields of Information Science and Administration and the importance that the context reveals for the current society of information and knowledge. Considered an interdisciplinary field, Information Science appropriates some paradigms and universes of the administration, and the latter also uses methodologies and results of Information Science researches for its own enrichment. In this way, the objective is to evaluate the volume of scientific production that involves the connection between Information Science and Administration between the years 2007 to 2017. For this, an exploratory research, of a qualitative nature, was carried out using the scientometric analysis technique. The results showed that practically all authors of the retrieved researches that involve the interdisciplinarity between Information Science and Administration also have interdisciplinary training between the areas. Finally, it is concluded that this field has the potential to become a kind of administrative science, however, since it is abusive to generalize the whole area as a possible management science, it is presumed that some axes of Information Science seek to support the field of Administration.
Keywords: Administration; Information science; interdisciplinarity; scientific production; Scientometrics